The Relationship Between The Distribution Of Private Investment Projects In The Syrian Governorates And Their Population: A Study Conducted In The Years 2007 To 2011 - زيـدان , رامي (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This article examines the relationship between the distribution of private investment projects established in the Syrian governorates, according to the laws governing investment in the private sector, and the distribution of the population in those governorates from 2007 to 2011. Through the study, the researcher has found that there is a defect between the distribution of projects and the distribution of the population. For this reason, the researcher made some proposals to activate and enable private investment projects in those governorates in a balanced manner, in a way that achieves justice in the governorates' share of projects that can be executed in the future, and that has a very important impact on the economic and social development process.